The Levels of Types of Intelligence of Players of Judo National Team of Jordan - Al-Odat , Jebreel; Malkieh , Yousef (Dirasat: Educational Sciences, 2020)
The study aims to identify the levels of intelligence in players of judo national team of Jordan. In addition, the study aims to identify the differences in the level of some types of multiple intelligences in the players depending on the variables of category of the team and the qualification of the player at the age of training. Due to the suitability and nature of this study, the scale of ownership (2016) was used as a tool for the study. The measure consists of (52) items divided into five types of multiple intelligences, namely: motor, linguistic, spatial, personal, and social. After confirming the validity and reliability of this tool, information was collected from a sample of 28 players. The results of the study showed that the level of the most common types of intelligence among the players is kinetic intelligence with an average of arithmetic (4.50), followed by spatial intelligence with an average of (4.24), personal intelligence with an average of (4.13) and linguistic intelligence with an average of (3.99). The results showed that there were no statistically significant differences in the number of different types of intelligence in the national judo team in Jordan depending on qualification and age of training variables. The researchers recommended some programs to develop and enhance the intelligence of the players of the national judo team in Jordan.